Upaya Meningkatkan Motorik Halus Anak Down Syndrome Melalui Aktivitas Melipat Kertas - Saba, Anselina Maria; Wahyuni, Sri (Jurnal Pelayanan Pastoral, 2023)
RJ is a child who has Down syndrome. In developing fine motor skills, RJ experienced problems due to low tone so that RJ was unable to carry out activities using his fingers. One of the children with down syndrome named rj had problems with his fine motor skills so that he could not do activities that involved his fingers properly according to his age. This study aims to determine the improvement of RJ's fine motor skills through origami paper folding activities. The research used is quantitative research with a single subject research method or known as single subject research with an A-B-A (Baseline-Intervention-Baseline) design. In the baseline-A1 condition, it was carried out for three sessions and was scored without intervention, in the Intervention-B condition, there were six sessions with intervention and a score was given, then the baseline phase A2 was repeated again with three activity sessions. The results obtained in the baseline A1 session received an average score of 26%, which means that the child's folding method is still in the untidy category, which means that their fine motor skills are not good. In the new intervention phase there was progress where on the first day of the intervention the results were 40% quite neat and at the end of the intervention session RJ obtained a score of 100% (very neat). To ensure that the ability to fold paper is good, a re-check was carried out for three sessions and in the last session a score of 94% was obtained even though it was below the results of the intervention phase but this was still in the very neat category. This is because children do it themselves without intervention.